Effect of turbulent inflows on airfoil performance for a Horizontal Axis Wind Turbine at low Reynolds numbers (part I: Static pressure measurement). (15th September 2016) - Li, Qing'an; Kamada, Yasunari; Maeda, Takao; Murata, Junsuke; Nishida, Yusuke
Abstract: This paper presented the results of a study to investigate the effect of turbulent inflows on the blade performance of a Horizontal Axis Wind Turbine (HAWT) by employing the experimental measurement at low Reynolds numbers. In order to observe the stall phenomenon, pressures on the rotor surface were measured by a multiport pressure device. Furthermore, for understanding the effects of different turbulence intensities on the aerodynamic performance characteristics of HAWT airfoil, static turbulence grids were used to adjust the turbulence intensity in wind tunnel. In this experiment, aerodynamic forces were discussed with different turbulence intensities and low Reynolds numbers. From comparing the results, it was found that the flow was separated at the leading edge in the case of without grids. On the other hand, in the case of turbulent flow field (with grids), the flow separated region was expanded gradually with the increase of the angle of attack. In the case of Re ≥ 1.5 × 10 5, compared with the low turbulence intensity, the lift coefficient was increased significantly at the high turbulent flow field. In addition, the drag coefficient in the turbulent flow field was reduced as compared to the low turbulence. Highlights: Surface pressures on the airfoil section were measured by a multiport pressure device. Static turbulence grids were used to adjust the turbulence intensity in wind tunnel. Stall phenomenon was discussed at different turbulence intensities and Reynolds numbers. The flow was separated at the leading edge without grids. In the cases of with grids, the flow separated region was expanded with the increase of angle of attack.